Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

I Simple Proof Question

  1. Jun 1, 2016 #1
    I am currently working my way though Calculus by Tom Apostol. One of the really early proofs ask the reader to prove: a(b-c)=ab-ac. Here is what I did, I let x=b-c which by the definition of subtraction equals x+c=b. Substituting that value into the right hand side I got a((x+c)-c)=a(x+(c-c))=a(x+0)=ax.

    I then plugged the exact same value into the right hand side getting a(x+c)-ac=(ax+ac)-ac=ax+(ac-ac)=ax.

    Is this sufficient as a proof? In a proof that I looked up the author of the proof instead let part of the left hand side =x and part of the right hand side equal y then showed that x=y. Is that the way I should have approached this problem?
  2. jcsd
  3. Jun 1, 2016 #2


    Staff: Mentor

    When you write a(x+c)-ac=(ax+ac)-ac don't you use already what you want to prove? Or is it all about the subtraction in the formula?
    You should start with a list of what you are allowed to use (and tell us). There is more than one possible way to establish group operations.
  4. Jun 1, 2016 #3
    Sorry let me fix it.
    Prove a(b-c)=ab-ac
    let x=b-c existence of subtraction (axiom)
    x+c=b (part of the subtraction axiom)
    a[(x+c)-c] substitution which is never spelled out but used repeatedly in books proofs so I assume its allowed
    a[x+(c-c)] associative property axiom
    a[x+0] existence of negatives axiom
    ax identity axiom

    For Right hand side
    ab-ac given
    a(x+c)-ac substitution as I did above
    (ax+ac)-ac distributive axiom
    ax+(ac-ac) associative axiom
    ax+0 existence of negative axiom
    ax identity axiom

    This shows both left hand side and right hand side =ax so both sides are equal.
  5. Jun 1, 2016 #4


    Staff: Mentor

    If you already have the distributivity for addition this is correct. But you could as well simply write
    $$a(b-c) = a(b+(-c))= ab + a (-c) = ab + a((-1)c) + ab + (a(-1))c = ab +(-a)c = ab-ac$$
    Edit: Maybe ## -c = (-1)c## is cheating here.
  6. Jun 3, 2016 #5
    Thanks so much for your help. That makes a lot of sense.
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted

Similar Discussions: Simple Proof Question
  1. Simple proof (Replies: 12)